PREDICTION OF RECURRENCE OF UTERINE FIBROIDS DURING PREGNANCY - N. N. Rozhkovskaya; D. M. Zhelezov; T. V. Kossei (Vіsnik Naukovih Doslіdžen', 2017)
Myoma of the uterus occurs in 15–45 % of women of reproductive age, thus occupying the second place in the structure of gynecological pathology. According to A. L. Karyakina, the main risk factors for uterine fibroids are women over 30, concomitant gynecological diseases, hypermenstrual syndrome, more than 2 abortions in anamnesis.